(3GdeDSSGJ GdUZjQI hGdeJhSWI aj EWGQgG GdfXQj hGdJWHjbj (B/s - (3YHO GddGhj, eMeO EHQGgjes ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2017)
(3ecGfI GdeDSSGJ GdUZjQI hGdeJhSWI aj GdJfejI GdGbJUGOjI,GdJLGQH GdOhdjI aj JYQja GdeDSSGJ GdUZjQI hGdeJhSWI,NUGFU hCgejI hOhQ GdeDSSGJ GdUZjQI hGdeJhSWI,GdYhdeI hGdeDSSGJ GdUZjQI hGdeJhSWI (B:(3GdJMOjGJ hGdaQU,GdJLGQH GdOhdjI GdfGLMI aj JCWjQ GdeDSSGJ GdUZjQI hGdeJhSWIs
(3HjHdjhZQGajG(B: (3U(B.175-181s
Keywords: (3GdeDSSGJ GdJLGQjIs